Control requirements for optimal operation of large isolated systems with increased wind power penetration - N. Hatziargyriou (1999)
Increased penetration of wind power in isolated systems may cause steady state and dynamic security problems incase of various disturbances. In this paper, initial results of studies of large systems with high wind penetrationare presented, revealing their control requirements in order to increase renewables, while maintaining a high levelof security of operation.